The Development and Application Evaluation of Meridian Energy Detection System in Traditional Oriental Medicine: A Preliminary Study - Ho, Wen-Chao; Chang, Yung-Hsien; Ng, Hui-Ping; Lee, Yu-Chen (Evidence-based complementary and alternative medicine, 2018)
As technology advances, more modern medical devices are developed to help the physicians in performing objective assessment and diagnosis. In this study, our main objective was to evaluate the clinical application of the low voltage Meridian Energy Detection System in assessing the electrodermal activity (EDA) of the specific acupoints in a specific age group of healthy individuals and to assess the difference in the energy overview between the genders and specific time of assessment. 43 young healthy adults were recruited in a single group, nonrandomized, evaluation study. Written informed consent of each participant was obtained prior to the assessments. Results on energy overview between genders and specific time of assessment as well as factors influencing EDA were discussed. It was concluded that the study using Meridian Energy Detection System in healthy individuals provided an understanding of the difference in energy level of the meridians between the genders. Male healthy individuals had significantly higher values for Physical Status as well as Yin and Yang energy while female healthy individuals had significantly higher values for Mental Health and Autonomic Nervous System. There was no significant difference when comparing the assessments at the specific time of assessment. Hence there was no specific time in using the device. However, due to the limitation of the sample size and the healthy subjects, future research can be designed to investigate whether the time of assessment can affect the results in individuals with specific disease conditions in larger scale. It may merit further studies on the application of such device as preliminary diagnosis of the overall conditions and investigate the treatment efficacy by observing the change in the meridian energy level.